Development Model of Psychoeducational Group based on Character Values of Palembang Sultanate Darussalam for High School Students in Palembang - Sucipto, Sigit Dwi; Harlina, Harlina; Putri, Rani Mega (Bulletin of Counseling and Psychotherapy, 2021)
The objectives of this study were: (1) to describe group guidance services and their implementation for high school students in Palembang; and (2) produce a group guidance model based on the Character Values of Palembang Sultanate Darussalam for High School Students in Palembang. This study used a research and development (R & D) method and design with the following steps: (1) a preliminary study and data collection; (2) research planning; (3) hypothetical model design; (4) validation of the hypothetical model; (5) model revision; (6) the final model. This study involved 2 guidance and counseling experts as expert validators and 5 guidance and counseling teachers as practitioner validators. Based on the results of research and discussion, the conclusions of this study are: (1) Group guidance services for high school students in Palembang are carried out discussing disagreed topics when the implementation of group guidance has started, and have not yet discussed the topic of the character values ​​of Palembang figures, and (2) a model of group guidance based on the Character Values of Palembang Sultanate Darussalam for High School Students in Palembang. consists of 7 (seven) components, namely rational, vision and mission, objectives, group counseling content, system support, group counseling stages, evaluation and follow-up.